On the performance of a high-order multiscale DG approach to LES at increasing Reynolds number. (15th November 2019) - de la Llave Plata, Marta; Lamballais, Eric; Naddei, Fabio
Highlights: We assess the robustness with increasing Reynolds number of a DG-LES approach. The effect of the numerical flux is studied on the Taylor-Green vortex configuration. DG-LES simulations of the cylinder flow at increasing Reynolds numbers are performed. Overall, the DG-VMS approach provides the best results. The benefit of using p-adaptation is demonstrated for the cylinder flow at Re=140000. Abstract: The variational multiscale (VMS) approach based on a high-order discontinuous Galerkin (DG) method is used to perform LES of the sub-critical flow past a circular cylinder at Reynolds 3 900, 20 000 and 140 000. The effect of the numerical flux function on the quality of the LES solutions is also studied in the context of very coarse discretizations of the TGV configuration at R e = 20 000 . The potential of using p -adaption in combination with DG-VMS is illustrated for the cylinder flow at R e = 140 000 by considering a non-uniform distribution of the polynomial degree based on a recently developed error estimation strategy [57]. The results from these tests demonstrate the robustness of the DG-VMS approach with increasing Reynolds number on a highly curved geometrical configuration.